FACTORS FROM #RACUNTIKTOK TRENDS, ONLINE CUSTOMER REVIEWS, ONLINE CUSTOMER RATINGS, AND FLASH SALES TO PURCHASE DECISIONS ON TIKTOK MARKETPLACE - Nurhikmah, Salma Tiana; Rahayu, Tri Septin Muji; Tubastuvi, Naelati Tubastuvi; Utami, Restu Frida Utami (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction This study aims to analyze the influence of #racuntiktok trends, online customer reviews, online customer ratings, and flash sales on purchasing decisions. Methods: The type of research using quantitative data was obtained through the distribution of questionnaires using Google Forms which were distributed through various social media platforms, with the student population of the University of Muhammadiyah Purwokerto. The technique used is purposive sampling as a method of retrieval to consider that the researcher sets special criteria such as TikTok users and have made purchases through the platform. The number of respondents as many as 158 people was determined using the roscoe formula. Furthermore, the collected data was analyzed using the Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) approach through SmartPLS 3 software. Results: The results showed that online customer reviews, online customer ratings, and flash sales had a positive and significant effect on purchase decisions, while #racuntiktok trends had no significant effect. Based on the results of research to increase sales on TikTok, sellers pay more attention to online customer reviews, online customer ratings and flash sales. Keywords: Trend #Racuntiktok, Customer Reviews, Online Customer Branches, Flash Sale, Purchase Results